The Influence of Emotional Intelligence on Teacher Performance through Work Motivation - Santoso, Herlambang Limantoro; Sugiyo; Awalya (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study aims to examine the influence of emotional intelligence on the performance of guidance and counseling teachers, with work motivation serving as a mediating variable. A quantitative approach was employed using a path analysis design supported by Hayes’ PROCESS Macro Model 4. The research sample consisted of 119 guidance and counseling teachers from various secondary schools in Ngawi regency, selected through multistage random sampling. The results indicate that emotional intelligence has a significant effect on guidance and counseling teachers’ performance (β = 0.276, p < 0.002) as well as on work motivation (β = 0.431, p < 0.001). In addition, work motivation significantly affects guidance and counseling teachers performance (β = 0.364, p < 0.001) and significantly mediates the relationship between emotional intelligence and guidance and counseling teachers performance (Estimate = 0.157, SE = 0.049, 95% CI [0.066, 0.274]). These findings confirm that enhancing guidance and counseling teachers’ performance can be achieved by strengthening emotional intelligence and work motivation, enabling teachers to provide counseling services that are more empathetic, effective, and professional.